COST-EFFECTIVENESS OF STRUCTURED EDUCATION IN CHILDREN WITH TYPE-1 DIABETES MELLITUS. (10th October 2016) - Basarir, Hasan; Brennan, Alan; Jacques, Richard; Pollard, Daniel; Stevens, Katherine; Freeman, Jennifer; Wales, Jerry; Price, Katherine
Abstract : Objectives: Kids in Control OF Food (KICk-OFF) is a 5-day structured education program for 11- to 16-year-olds with type 1 diabetes mellitus (T1DM) who are using multiple daily insulin injections. This study evaluates the cost-effectiveness of the KICk-OFF education program compared with the usual care using data from the KICk-OFF trial. Methods: The short-term within-trial analysis covers the 2-year postintervention period. Data on glycated hemoglobin (HbA1c), severe hypoglycemia, and diabetic ketoacidosis (DKA) were collected over a 2-year follow-up period. Sub-group analyses have been defined on the basis of baseline HbA1c being below 7.5 percent (58.5 mmol/mol) (low group), between 7.5 percent and 9.5 percent (80.3 mmol/mol) (medium group), and over 9.5 percent (high group). The long-term cost-effectiveness evaluation has been conducted by using The Sheffield Type 1 Diabetes Policy Model, which is a patient-level simulation model on T1DM. It includes long-term microvascular (retinopathy, neuropathy, and nephropathy) and macrovascular (myocardial infarction, stroke, revascularization, and angina) diabetes-related complications and acute adverse events (severe hypoglycemia and DKA). Results: The most favorable within-trial scenario for the KICk-OFF arm led to an incremental cost-effectiveness ratio (ICER) of £23, 688 (base year 2009) with a cost-effectiveness probability of 41.3 percent. Simulating the long-term complications using the full cohort data, the mean ICER for the base case was £28, 813 (base year 2011) and the probability of the KICk-OFF intervention being cost-effective at £20, 000/QALY threshold was 42.6 percent, with considerable variation due to treatment effect duration. For the high HbA1c sub-group, the KICk-OFF arm was "dominant" (meaning it provided better health gains at lower costs than usual care) over the usual care arm in each scenario considered. Conclusions: For the whole study population, the cost-effectiveness of KICk-OFF depends on the assumption for treatment effect duration. For the high baseline HbA1c sub-group, KICk-OFF arm was estimated to be dominant over the usual care arm regardless of the assumption on the treatment effect duration.